2004
DOI: 10.1897/02-281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vision® herbicide on mortality, avoidance response, and growth of amphibian larvae in two forest wetlands

Abstract: The effects of Vision (glyphosate, 356 mg acid equivalents (a.e.)/L) on mortality, avoidance response, and growth of larval amphibians (Rana clamitans and Rana pipiens) were investigated using in situ enclosures deployed in two forest wetlands of northern Ontario, Canada. In addition to untreated controls, Vision was applied to yield initial concentrations ranging from 0.29 to 14.3 mg a.e./L (0.94-46.1 mg/L of Vision). Resultant 96-h median lethal concentration (LC50) values ranged from 2.70 to 11.5 mg a.e./L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 40 publications
6
63
1
2
Order By: Relevance
“…Toxicity of frog embryos and tadpoles was less in the microcosms than in laboratory tests. The reason for this may be attributed to the presence of sediments and organic matter which rapidly adsorb the glyphosate (Relyea, 2004;Tsui & Chu, 2004;Wojtaszek et al, 2004) and surfactants such as POEA (Wang et al, 2005). In addition, residues of glyphosate decline rapidly within 24h after application (Trumbo, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicity of frog embryos and tadpoles was less in the microcosms than in laboratory tests. The reason for this may be attributed to the presence of sediments and organic matter which rapidly adsorb the glyphosate (Relyea, 2004;Tsui & Chu, 2004;Wojtaszek et al, 2004) and surfactants such as POEA (Wang et al, 2005). In addition, residues of glyphosate decline rapidly within 24h after application (Trumbo, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The life cycle and physiological characteristics of amphibians make them particularly susceptible to all environmental stressors (Cowman & Mazanti, 2000). Glyphosate formulations have been considered to induce genotoxic, morphological, biochemical, and physiological effects to anurans (Clements, Ralph, & Petras, 1997;Lajmanovich, Lorenzatti, Maitre, Enrique, & Peltzer, 2003;Cauble & Wagner, 2005;Bernal, Solomon, & Carrasquilla, 2009a;Mann, Hyne, Choung, & Wilson, 2009;Lenkowski, Sanchez-Bravo, & Mclaughlin, 2010;Williams & Semlitsch, 2010;Lajmanovich, Attademo, Peltzer, Junges, & Cabagna, 2011;Relyea, 2012), although low toxicity has been reported under realistic field conditions (Howe et al, 2004;Wojtaszek, Staznik, Chartrand, Stephenson, & Thompson, 2004;Bernal, Solomon, & Carrasquilla, 2009b). Other studies have concluded that the glyphosate and its formulated products represent moderate (Giesy, Dobson, & Solomon, 2000;Sparling, Linder, Bishop, & Krest, 2010) or negligible risk to aquatic organisms (World Health Organization International Program on Chemical Safety, 1994; Giesy et al, 2000;Solomon & Thompson, 2003).…”
mentioning
confidence: 99%
“…Among the many abiotic stressors that could interact with glyphosate, only pH has been manipulated. In these studies, glyphosate with POEA became substantially more lethal to larval amphibians at higher pH [15,16,18]. Among the many biotic stressors, one study has manipulated the stress of predation risk and found that glyphosate with POEA became more lethal in the presence of chemical cues emitted by predators [6].…”
Section: Introductionmentioning
confidence: 99%
“…Coincident biomonitoring showed no significant toxic effects on two species of sensitive amphibian larvae caged within the multiple wetlands under study. Furthermore, in situ enclosure field studies in either ponds in northern Ontario or in small wetlands in New Brunswick Canada, showed no significant effects on amphibian survival, growth or development when directly exposed to formulated glyphosate-based herbicides even at the maximum permissible label rates [77,78,90,91]. These results were similar to a field study in Oregon USA, assessing the effects of clear-cutting and clear-cutting followed by glyphosate application where no herbicide effects were observed for six species of amphibians [92].…”
Section: Direct Effectsmentioning
confidence: 99%
“…The high adsorption capacity of sediment for glyphosate has frequently resulted in higher peak concentrations in sediments compared with water (Table 3), that persisted for longer periods of time, even when the active ingredient was present in only small quantities in the water column (Table 3). It is likely that this process is a primary pathway for removal of glyphosate from the water column in forested freshwater environments [52,56,73,77,78].…”
Section: Fate In the Aquatic Environmentmentioning
confidence: 99%